Treatment And Conservation Of An Oil Painting Of The King Fouad I From The 20th Century At The Egyptian National Archives - Abdel-Rahman EL-SROUGY (Fayoum University, 2015)
This paper aims to conduct an analytical study to identify the components of an oil painting (using microscopy, XRD, XRF and FTIR), determine the deterioration factors and phenomena (especially the manmade) and apply the necessary conservation treatments (fumigation, cleaning, filling, consolidation). The paint canvas is a portrait of the King Fouad Istored at the Egyptian National Archives.